A note on the spectral operators of scalar type and semigroups of bounded linear operators - Marat V. Markin (International Journal of Mathematics and Mathematical Sciences)
It is shown that, for the spectral operators of scalar type, the well-known characterizations of the generation of C0- and analytic semigroups of bounded linear operators can be reformulated exclusively in terms of the spectrum of such operators, the conditions on the resolvent of the generator being automatically met and the corresponding semigroup being that of the exponentials of the operator.